2011
DOI: 10.1155/2011/483728
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Immunosuppressive Potential of Calcineurin Inhibitor-Sparing Regimens in Liver Transplant Recipients with Impaired Renal Function

Abstract: Patients requiring liver transplantation (LT) frequently experience renal insufficiency (RI), which affects their survival. Although calcineurin inhibitor-sparing immunosuppressive regimens (CSRs) are well known to prevent RI, the immune state in recipients receiving CSR remains to be intensively investigated. Among 60 cases of living-donor LT at our institute, 68% of the patients had none to mild RI (non-RI group) and 32% of the patients had moderate to severe RI (RI group). The RI group received a CSR compri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…The basic immunosuppressive regimen used following LDLT has been described . In brief, the immunosuppressive regimen consisted of tacrolimus (TAC) and methylprednisolone (MP) with gradual tapering of the dose.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The basic immunosuppressive regimen used following LDLT has been described . In brief, the immunosuppressive regimen consisted of tacrolimus (TAC) and methylprednisolone (MP) with gradual tapering of the dose.…”
Section: Methodsmentioning
confidence: 99%
“…As routine Treg analysis had only recently commenced, we analyzed Treg frequency in the patients from our cohort. Tregs were surface stained with the following fluorochrome‐conjugated monoclonal antibodies from BD Pharmingen: peridinin‐chlorophyll protein‐Cyanine5.5 anti‐human CD3 (SK7), allophycocyanin‐conjugated Cyanine7 anti‐human CD4 (RPA‐T4), fluorescein isothiocyanate‐conjugated anti‐human CD25 (M‐A251), PE‐Cyanine7 anti‐human CD45RA (HI100). Intracellular Foxp3 was stained using PE‐conjugated anti‐human Foxp3 (PCH101; eBioscience).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical suspicion of TCMR was supported by the protocoled MLR assay, which can rigorously monitor rejection. (16)(17)(18) Episodes of rejection…”
Section: Definition and Treatment Of Tcmrmentioning
confidence: 99%
“…We have previously reported that optimization of immunosuppressive therapy based on the CFSE-MLR assay provides a low incidence of acute rejection, reduction of infectious complications, and helps in monitoring anti-self-response of CD4 + T cells, which predicts the recurrence of autoimmune liver diseases after LT ( 98 , 100 102 ) ( Figure 3B ). In addition, CFSE-MLR-based immune monitoring has been proven to be a useful tool to personalize IS therapy, especially for LT patients with impaired renal function and HBV-infected LT patients requiring post-transplant HBV vaccination ( 103 , 104 ). The benefit of CFSE-MLR immune-monitoring can be applied to T cell receptor (TCR) repertoire analysis by high-throughput sequencing.…”
Section: Immune Monitoring To Personalize Immunosuppression Toward Tomentioning
confidence: 99%